2019
DOI: 10.1007/s11524-019-00394-w
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Consequences of Sexual Misconduct by Law Enforcement and Criminal Justice Personnel among Black Drug-Involved Women in Community Corrections

Abstract: This study examines the prevalence, correlates, and mental health consequences of sexual misconduct by law enforcement and criminal justice (LECJ) personnel. Baseline data for Project E-WORTH (Empowering African-American Women on the Road to Health) were collected between November 2015 and May 2018 from 351 drug-involved Black women from community corrections in New York City. LECJ sexual misconduct was self-reported and we measured mental health outcomes with the CESD-4 and the PTSD Checklist. Univariate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Some of these issues were pre-existing, although they may have been exacerbated by the APSP. Although victim outcomes of sexual misconduct in police officers remain largely unexplored, recent US research has found a link between sexual misconduct and resultant adverse mental health in victims (Stringer et al, 2020). This echoes the findings of general research into sexual assault and increased reporting of depression, suicidal ideation and post-traumatic stress disorder (Brooker et al, 2018; DiMauro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these issues were pre-existing, although they may have been exacerbated by the APSP. Although victim outcomes of sexual misconduct in police officers remain largely unexplored, recent US research has found a link between sexual misconduct and resultant adverse mental health in victims (Stringer et al, 2020). This echoes the findings of general research into sexual assault and increased reporting of depression, suicidal ideation and post-traumatic stress disorder (Brooker et al, 2018; DiMauro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that victims of APSP by police often suffer adverse outcomes to their mental health, namely post-traumatic stress disorder and depression (Stringer et al, 2020). One study finds that sexual abuses by police officers may also be associated with an increased risk of victim suicide (DeVylder, Frey, Cogburn, Wilcox, Sharpe, Oh, Nam & Link, 2017).…”
Section: Victimsmentioning
confidence: 99%
“…The direct and indirect effects of this exposure to such police abuse may be multifold. As suggested by prior research (Stringer et al, 2019), abuse by law enforcement and community corrections increases the likelihood of depression, anxiety and trauma as well as physical pain that may trigger cravings for self-medication resulting in drug misuse and overdose. At the same time, fear of experiencing such abuse may inhibit women from calling police during violent or overdose incidents that may further increase their exposure to both violence and overdose (Blankenship et al, 2018).…”
Section: Np21516mentioning
confidence: 94%
“…Often, victims of PSM are highly vulnerable members of society with histories of drug abuse, sexual abuse and mental health issues (Cottler et al, 2014; Sweeting et al, 2020). Adverse outcomes for victims who are external to the police include depression and post-traumatic stress disorder (Stringer et al, 2020). Police sexual misconduct can also occur between colleagues in the form of inappropriate sexualised language and overfamiliar touching (Brown et al, 2019).…”
Section: Introductionmentioning
confidence: 99%